Report of the President (Econometrica, 2002)
(Continued on page 2) I want to thank the members of the Auditing Section for giving me the opportunity to serve as the president of the Auditing Section. It is a great honor and I will do my best to meet the high standards set by the Past President, Stan Biggs, and his predecessors. I thoroughly enjoyed my year as Vice President–Academic and was continually amazed by the work that needed to be done and the enthusiasm and competence with which the Executive Committee performed its work. On behalf of the Auditing Section, I would like to thank the following outgoing members of the Executive Committee for their outstanding service: Karen Pincus, Past President; Mark Beasley, Treasurer; and Jack Robertson, Historian. Each of these individuals has worked hard for the Section and its members for many years. I would also like to welcome three new members of the Executive Committee: Joe Carcello, Vice President–Academic; Rick Tubbs, Treasurer; and Andy Bailey, Historian. Continuing members are Stan Biggs, Past President; Abe Akresh, Vice President–Practice; and Audrey Gramling, Secretary. I am very fortunate to have the opportunity to work with such distinguished colleagues. The Auditing Section was well represented at the AAA Annual Meeting in Atlanta. There were 27 auditing papers in concurrent sessions, 12 forum papers, and two panel sessions. The papers were of excellent quality and, as best I could tell, the sessions were well attended. Thanks go out to Robin Roberts, Director of the 2001 Annual Meeting Committee; Randy Elder, Assistant Director; Dana Hermanson, CPE Director; and the 67 volunteers who reviewed the 72 submitted papers. Randy Elder, Director of the 2002 Annual Meeting Committee, has a call for submissions in this issue and Bill Heninger has a call for CPE proposals. Remember that the number of concurrent sessions our section is assigned is a function of the number of papers submitted to the Annual Meeting. Our representation at the Annual Meeting is in your hands! The Executive Committee met twice in Atlanta, bringing closure to several projects from last year. These included the evaluation of the Section’s committee structure and operations, and the related revision of the Section’s operating manual. Jack Robertson has done a great job reorganizing the operating manual. Under Stan’s leadership, the Section’s committee structure has been considerably streamlined. The result should be more effective and efficient Section operations. Under the new committee structure, standing committees generally have a chairperson and six members who have staggered two-year terms. The awards committees are yearly appointments. Terms of the various program committees vary, but the committee chair first serves as vice chair and then a third year as past chair to provide the committee with continuity. Figure 1 outlines the Section’s committees. You can find additional information about these committees and all of the Section’s positions using links on the Section’s home page. The year 2001–2002 is a transition year to this new committee structure, and as a result, some committees had no new members this year. This is one reason that some volunteers for this year’s committees could not be offered positions.